2015
DOI: 10.1073/pnas.1422371112
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of Sertoli cells to fetal-like Leydig cells by Wt1 ablation

Abstract: Sertoli and Leydig cells, the two major somatic cell types in the testis, have different morphologies and functions. Both are essential for gonad development and spermatogenesis. However, whether these cells are derived from the same progenitor cells and the mechanism regulating the differentiation between these two cell types during gonad development remains unclear. A previous study showed that overactivation of Ctnnb1 (cadherin-associated protein, beta 1) in Sertoli cells resulted in Sertoli cell tumors. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 35 publications
(44 reference statements)
2
68
0
1
Order By: Relevance
“…Because endogenous WT1 expression in the somatic compartment of the testis becomes restricted to Sertoli cells within the testis cords after E12.5, WT1 could be involved in the maintenance of Sertoli cell identity. In line with this hypothesis, ablation of Wt1 gene in Sertoli cells results in the transformation of Sertoli cells into fetal Leydig-like cells, whereas overexpression of Wt1 in fetal Leydig cells promotes the expression of Sertoli cell-specific genes and suppresses steroidogenic genes (Wen et al, 2014;Zhang et al, 2015). WT1 appears to mediate the cell fate determination of the common progenitor cells to become either Sertoli cells or fetal Leydig cells.…”
Section: Wt1mentioning
confidence: 68%
“…Because endogenous WT1 expression in the somatic compartment of the testis becomes restricted to Sertoli cells within the testis cords after E12.5, WT1 could be involved in the maintenance of Sertoli cell identity. In line with this hypothesis, ablation of Wt1 gene in Sertoli cells results in the transformation of Sertoli cells into fetal Leydig-like cells, whereas overexpression of Wt1 in fetal Leydig cells promotes the expression of Sertoli cell-specific genes and suppresses steroidogenic genes (Wen et al, 2014;Zhang et al, 2015). WT1 appears to mediate the cell fate determination of the common progenitor cells to become either Sertoli cells or fetal Leydig cells.…”
Section: Wt1mentioning
confidence: 68%
“…Our recent study demonstrated that inactivation of Wt1 in Sertoli cells after sex determination using AMH-Cre mice resulted in the transformation of Sertoli cells to Leydig cells, suggesting that Sertoli and Leydig cells are probably derived from same progenitor cells (Zhang et al, 2015). In control ovary, 3β-HSD-positive thecainterstitial cells are not observed during the embryonic stage.…”
Section: Discussionmentioning
confidence: 97%
“…Our previous study showed that inactivation of Wt1 in Sertoli cells after sex determination using AMH-Cre mice caused testicular cord disruption (Gao et al, 2006) and Sertoli cells can be reprogrammed into Leydig cells (Gao et al, 2006;Zhang et al, 2015). These studies indicate that Wt1 plays important roles in testis development and Sertoli cell lineage maintenance.…”
Section: Introductionmentioning
confidence: 94%
“…Sertoli cells can also be reprogrammed to generate functional neurons (Sheng et al 2012) and other cell lineages (e.g. Leydig cells and iPS cells) (Zhang et al 2015) and thus they can have potential clinical value in translation medicine. Furthermore, these cell lines could be exploited to uncover the underlying etiology of male infertility (e.g.…”
Section: Spermatocyte Line Immortalized With a Specific Promoter-basementioning
confidence: 99%
“…Sertoli cells can be reprogrammed to pluripotent stem cells (Sun et al 2014), and significantly they are directly converted to morphologic, phenotypic and functional neural stem cells (Sheng et al 2012) and Leydig cells (Zhang et al 2015). Moreover, Sertoli cells are engineered to produce certain proteins that restore cell metabolic function (Kaur et al 2014).…”
Section: Introductionmentioning
confidence: 99%